Altered Gut Microbiota and Immunity Defines Plasmodium vivax Survival in Anopheles stephensi - Sharma, Punita; Rani, Jyoti; Chauhan, Charu; Kumari, Seena; Tevatiya, Sanjay; Das De, Tanwee; Savargaonkar, Deepali; Pandey, Kailash C.; Dixit, Rajnikant (Frontiers in Immunology, 2020)
Blood feeding-enriched gut-microbiota boosts mosquitoes’ anti-Plasmodium immunity. Here, we ask how Plasmodium vivax alters gut-microbiota, anti-Plasmodial immunity and impact tripartite Plasmodium-mosquito-microbiota interactions in the gut lumen. We used a metagenomics and RNAseq strategy to address these questions. In naïve mosquitoes Elizabethkingia meningitis and Pseudomonas sps. are the dominant bacteria and blood-feeding leads to heightened detection of Elizabethkingia, Pseudomonas and Serratia 16s RNA. A parallel RNAseq analysis of blood-fed midguts also shows the presence of Elizabethkingia-related transcripts. Post, a Plasmodium vivax infected blood-meal, however, we do not detect bacterial 16sRNA until circa 36 hours. Intriguingly, transcriptional expression of a selected array of antimicrobial arsenal cecropins 1-2, defensin-1 and gambicin remain low during the first 36 hours– a time frame when ookinetes/early oocysts invade gut. We conclude during the preinvasive phase, Plasmodium vivax outcompetes midgut-microbiota. This microbial suppression likely negatively impacts mosquito immunity which in turn may enhance Plasmodium vivax survival. Detection of sequences matching to mosquito-associated Wolbachia opens a new inquiry for its exploration as an agent for ‘paratransgenesis-based’ mosquito control.